Correlates of excessive daytime sleepiness in de novo Parkinson's disease: A case control study. Issue 10 (11th June 2015) - Simuni, Tanya; Caspell‐Garcia, Chelsea; Coffey, Christopher; Chahine, Lama M.; Lasch, Shirley; Oertel, Wolfgang H.; Mayer, Geert; Högl, Birgit; Postuma, Ron; Videnovic, Aleksandar; Amara, Amy Willis; Marek, Ken; et al.
Abstract Objective This study was undertaken to determine the frequency and correlates of excessive daytime sleepiness in de novo, untreated Parkinson's disease (PD) patients compared with the matched healthy controls. Methods Data were obtained from the Parkinson's Progression Markers Initiative, an international study of de novo, untreated PD patients and healthy controls. At baseline, participants were assessed with a wide range of motor and nonmotor scales, including the Movement Disorder Society Unified Parkinson's Disease Rating Scale (MDS‐UPDRS). Excessive daytime sleepiness was assessed based on the Epworth Sleepiness scale (ESS), with a cutoff of 10. Results Four hundred twenty‐three PD subjects and 196 healthy controls were recruited into the study. Mean ESS (min, max) score was 5.8 (0, 20) for the PD subjects and 5.6 (0, 19) for healthy controls (P = 0.54). Sixty‐six (15.6%) PD subjects and 24 (12%) healthy controls had ESS of at least 10 (P = 0.28). No difference was seen in demographic characteristics, age of onset, disease duration, PD subtype, cognitive status, or utilization of sedatives between the PD sleepiness‐positive versus the negative group. The sleepiness‐positive group had higher MDS‐UPDRS Part I and II but not III scores, and higher depression and autonomic dysfunction scores. Sleepiness was associated with a marginal reduction of A‐beta (P = 0.05) but not alpha‐synuclein spinal fluid levels in PD. Conclusions This largest case control study demonstrates no difference in prevalence of excessive sleepiness in subjects with de novo untreated PD compared with healthy controls. The only clinical correlates of sleepiness were mood and autonomic dysfunction. Ongoing longitudinal analyses will be essential to further examine clinical and biological correlates of sleepiness in PD and specifically the role of dopaminergic therapy. © 2015 International Parkinson and Movement Disorder Society